Synthesis of Some Biologically Active Pyrazolylphthalazine Derivatives and Acyclo-C-nucleosides of 6-(2,4,6-trimethylphenyl)-1,2,4-triazolo[3,4-a]phthalazine - E. El-Shamy, Ibrahim; Abdel-Mohsen, A.M.; M.G. Fouda, Moustafa; S. Al-Deyab, Salem; A. El-Hashash, Maher (Asian Journal of Chemistry, 2014)
1-Chloro-4-(2,4,6-trimethylphenyl)phthalazine (2) was used as a precursor for preparation of some novel pyrazolylphthalazine derivatives 6-13 and 15-19. Moreover, the acyclonucleosides 20-23 a-e were prepared by the reaction of hydrazinophthalazine derivative 3 with different aldoses. All new phthalazine derivatives were characterized using 1H NMR, 13C NMR, FTIR, mass spectrum and elemental analysis. The newly synthesized compounds showed highly activity against different species of bacteria and fungi, in addition to an excellent antiinflammatory property.